creating clouds with teachers and students during the pandemic - da costa, luciano bedin; mesquita corrêa, tatiele (childhood & philosophy, 2024)
This essay presents the results of a master’s dissertation research from the Post-Graduate Program on Social and Institutional Psychology of the Federal University of Rio Grande do Sul (UFRGS). Carried out between 2020 and 2022 during the COVID-19 pandemic, the research followed the execution of the extension project Carta ao mundo que vem (Letter to the world to come), which aimed to create a collective letter involving students and teachers from pre-schools and elementary schools from Rio Grande do Sul, Bahia and Portugal. The strategy to approach students and institutions was implemented remotely, being clouds an important figure as a digital storage system (where it’s possible to store data in clouds) and as an inhabitant of the sky (always there for those who are willing to look up). This essay stems from two questions: 1) “how to research in pandemic times?”; 2) “how to create collectively with people who do not know each other?”. In the attempt to answer these questions, we seek to present some research cartographic movements, resulting in six clouded clues: 1) what do we want to store in the cloud?; 2) what does a cloud taste like?; 3) what happens in a cloud?; 4) what can you see from this cloud?; 5) what was the world like before the pandemic?; 6) what was school like during the pandemic? Beyond the answers, we are interested in the potential of each of these clues and questions that, just like clouds, still hover in the air.